Philosophy for understanding theology - Allen, Diogenes; Springsted, Eric O. (Louisville, Westminster John Knox Press, 2007)
"This new edition of Philosophy for Understanding Theology adds chapters on postmodernism and questions of the self and the good to bring the book up to date with current scholarship. It introduces students to the influence that key philosophers and philosophical movement through the centuries have had on shaping Christian theology in both its understandings and forms of expression."--Jacket
Plato: the world is the handiwork of a mind -- Plato: this world is not our home -- The platonic tradition: the stoics, plotinus, pseudo-dionysius -- Aristotle: his categories and the mystery of god --
Includes bibliographical references (pages 257-259) and index.
Keywords: Philosophical theology; Philosophy -- History; Christianity -- Philosophy